Sustainable water purification - Rahman, M. Safiur; Islam, Rafiqul, 1959- (Wiley-Scrivener, 2020)
"Water is synonymous with life. This has been the case since pre-historic time to the modern era. For the first time, humanity faces a crisis that eclipses the energy crisis, which has often incapacitated the global economy. The Climate-Water-Food nexus epitomizes our current civilization that depends on energy as the driver. Many recognize this crisis as a product of fossil fuel production, which allegedly triggered climate change and the "climate change debate." Others predict the onslaught of "water wars" in the coming decades. As the world gears up to another lineup of empty promises and ensuing chaos, this book turns this crisis on its head and shows the source of the water crisis. The science behind the water cycle is described in clear language, without resorting to dogmatic assertions and spurious assumptions. The role of the sun, natural carbon dioxide (CO2) and water and the need to maintain natural processes free from artificial chemicals are discussed in detail. The book makes it clear how most of the currently used purification techniques violates the natural cycle involving sunlight, CO2 and water, and thus become unsustainable. A series of water purification techniques, as usable for drinking, agricultural and industrial applications are presented. The advantages of these techniques and their long-term sustainability are highlighted, with discussion on improvements in the future. Whether for the engineer or scientist working in the field or laboratory or the student, this is a must-have for any engineer, scientist, student, or policymaker."-- Provided by publisher.
Keywords: Water -- Purification.; Sustainability.; elektronické knihy; electronic books